Factors Predictive of Adverse Events Associated with Endoscopic Ultrasound-Guided Fine Needle Aspiration of Pancreatic Solid Lesions - Katanuma, Akio (Springer US, 2013)
BACKGROUND: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) provides high diagnostic accuracy with a low incidence of procedural complications. However, it occasionally causes serious complications, and factors that increase the susceptibility to such adverse events remain unknown. AIMS: We aimed to examine post-procedural events and determine risk factors associated with EUS-FNA of pancreatic solid lesions. METHODS: This single-center retrospective study included 316 consecutive patients with pancreatic solid lesions who underwent 327 EUS-FNA procedures from April 2003 to September 2011. We registered all patients undergoing EUS-FNA in the database and retrospectively ascertained the presence/absence of post-procedural adverse events. RESULTS: The incidence of post-procedural adverse events, including moderate to mild pancreatitis, mild abdominal pain, and mild bleeding, was 3.4 %. Univariate analysis showed that the incidence of post-procedural events was significantly increased in patients with tumors less than or equal to 20 mm in diameter (P < 0.001), those with pancreatic neuroendocrine tumors (PNET) (P = 0.012), and patients who had intervening normal pancreas for accessing the lesion (P = 0.048). Multivariate analysis identified tumors measuring less than or equal to 20 mm in diameter (OR 18.48; 95 % CI 3.55–96.17) and case of PNETs (OR 36.50; 95 % CI 1.73–771.83) were an independent risk factors. CONCLUSIONS: EUS-FNA of pancreatic solid lesions is a safe procedure. However, pancreatic lesions with small diameters and pancreatic neuroendocrine tumors are important factors associated with adverse events after EUS-FNA.